Unleashing the Power of LAPS-Heuristic Learning: Enhancing Mathematical Problem Solving Abilities in Grade 3 Students : Melepaskan Kekuatan Pembelajaran LAPS-Heuristik: Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Kelas 3 - Putra, Deni Adi; Faradita, Meirza Nanda; Anita, Vebri (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine whether there is a significant influence between the mathematical problem solving abilities of students who are given the LAPS-Heuristic learning model and those who are not given the LAPS-Heuristic learning model. This type of research is experimental research with a quantitative descriptive approach. The subjects of this study were all grade 3 students of MI Mahir Ar Riyadl for the 2021/2022 academic year. The results show that there is a significant value (2-tailed) in the first row of 0.000 and it can be seen that 0.000 <0.05, so that H_1 is accepted, which means that there is a significant influence between students' mathematical problem solving abilities using the LAPS-Heuristic learning model with those who do not use the LAPS-Heuristic model. This means that in this study it can be concluded that there is an effect of applying the LAPS-Heuristic model to students' mathematical problem solving abilities. Suggestions from this study are the LAPS-Heuristic learning model so that it can be applied to other subjects and materials.